2017
DOI: 10.1155/2017/1318945
|View full text |Cite
|
Sign up to set email alerts
|

Spatial-Temporal Similarity Correlation between Public Transit Passengers Using Smart Card Data

Abstract: The increasing availability of public transit smart card data has enabled several studies to focus on identifying passengers with similar spatial and/or temporal trip characteristics. However, this paper goes one step further by investigating the relationship between passengers' spatial and temporal characteristics. For the first time, this paper investigates the correlation of the spatial similarity with the temporal similarity between public transit passengers by developing spatial similarity and temporal si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 32 publications
0
26
0
Order By: Relevance
“…The trip similarity is examined in two parallel steps of the spatial and temporal similarity measures. Both spatial and temporal similarity measures are adopted from Faroqi et al [15] where more details can be found. The measures are developed specifically for smart card dataset that include boarding and alighting transactions (not like GPS trajectories that include measurements every few meters).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The trip similarity is examined in two parallel steps of the spatial and temporal similarity measures. Both spatial and temporal similarity measures are adopted from Faroqi et al [15] where more details can be found. The measures are developed specifically for smart card dataset that include boarding and alighting transactions (not like GPS trajectories that include measurements every few meters).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, a passenger can have one or more trips during a day, all of which should be considered in measuring the spatial or temporal similarity with other passengers. Spatial and/or temporal similarity measures between passengers based on their trips can be used as a measure to study the closeness or relationship between the passengers [15]. Therefore, to have a comprehensive insight of travel patterns, both spatial and temporal dimensions of the trips should be considered in the clustering of the passengers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Briand et al [17] analyzed the behavioral habits of public transport passengers using a real dataset of smart card data covering a period of five years. Faroqi et al [18] investigated the relationship between passengers' spatial and temporal characteristics with a novel passenger-based perspective using smart card data. It is implemented for fourday smart card data including 80,000 passengers in Brisbane, Australia.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Hamed et al [12] investigated the relationship between the spatial and temporal characteristics of public transit passengers, by using four days' worth of smart-card data from 80,000 passengers in Brisbane, Australia. Hamed et al developed measures of spatial and temporal similarity with a perspective on new passengers, in which passengers were able to travel multiple times within the network.…”
Section: Smart-card Datamentioning
confidence: 99%